Africa and the Americas in the Columbian Exchange: an Interview with Judith Carney - Leal, Claudia; Van Ausdal, Shawn; Miraglia, Marina Miraglia; Dutra e Silva, Sandro (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
Africa and the Americas in the Columbian Exchange: an Interview with Judith Carney